Women Leading in Education Across the Continents - Macha, Hildegard; Bauer, Quirin J. (My University, 2010)
Scholars across the globe created the Women Leading in Education Across the Continents (WLE) group at a conference held in Rome in 2007. The goal was to fill a knowledge vacuum; an understanding of the status of women in educational leadership, in both basic and higher education, from both a qualitative and quantitative view. The group emerged with the following goals: to gather data from an increasing number of countries across all continents regarding the number of women represented in positions of leadership in education; to describe issues that are either barriers or facilitators regarding the ability of women to attain the highest levels of educational leadership; to bring those issues to life through an analysis of the lives and stories of women within the group; to impact research, policy making and practice through publications and an online gender audit.
Keywords: Bildung; Frauen; Strategies of Leadership and Power; Women and Education; Women Leading in Education; ddc:300